A mixed methods exploration of self-presentation, authenticity, and role model function on Instagram: perspectives from female influencers in Germany - Zimmermann, Daniel; Schneider, Colleen; Kaspar, Kai (Frontiers in Psychology, 2025)
IntroductionSocial media influencers focussing on beauty, fashion, and fitness topics (BFFI) are important opinion leaders on Instagram. Nevertheless, they are criticized for their potential negative influence on their followers' physical and mental health due to their potentially biased self-presentation. Previous research has mainly focused on followers' perceptions of influencers' self-presentation, leaving a gap regarding the influencers' views.MethodThe present survey included 26 female BFFIs from Germany (18–35 years old), with 16 self-reported micro-influencers (10,000–100,000 followers) and ten macro-influencers (>100,000 followers), representing (semi-)professionals in this domain. 17 influencers saw their main focus in the field of fitness, 16 in fashion, and 13 in beauty. The survey included demographic information, open-ended questions, established and self-developed rating scales, and a social desirability assessment to examine the BFFIs' perceptions of their goals, self-presentation, and role model function. Quantitative data was examined via inter-correlation matrix and ANOVA, and qualitative data was analyzed via an established approach for qualitative content analysis.ResultsInfluencers pursue mostly self-realization (50% of participants gave at least one related answer) and commercial goals (50%). While they generally perceive their self-presentation as authentic (84.6%) and positive (76.9%), they still see room for improvement in content creation (61.5%) and self-presentation (30.8%). Fear of negative feedback, absence of positivity and motivation, wrong cooperation partners (30.8% each) and insecurity (23.1%), among others, may lead to a less authentic self-presentation and use of picture editing. The tendency toward socially desirable responses (impression management) is negatively connected to the reported frequency of image editing tools used and attempts to appear authentic. Influencers reported several examples of responsible and irresponsible behaviors and strategies to avoid negative effects on their followers. The type of influencer (micro or macro level) showed a significant effect on the importance attributed to one's own role as an influencer.DiscussionThe complex findings suggest potential conflicts between the influencers' goals and the expectations of followers and cooperation partners. Influencers find themselves in a dual role as users and producers. This results in concrete behavioral challenges for them, but also in implications for established theories of media use.